Bio-precipitates produced by two autochthonous boron tolerant Streptomyces strains - Moraga, Norma Beatriz (2017)
Boron is widespread in the environment. Although contaminated soils are hard to recover different strategies have been investigated in the recent years. Bioremediation is one of the most studied because it is eco-friendly and less costly than other techniques. The aim of this research was to evaluate whether two Streptomyces strains isolated from boron contaminated soils in Salta, Argentina, may help remove boron from such soils. For this, they were grown in different liquid media with two boric acid concentrations and their specific growth rate and specific boric acid consumption rate were determined. Both strains showed great capacity to remove boron from the media. Increasing boric acid concentrations affected negatively the specific growth rate, however the specific boric acid consumption rate was superior. Boron bio-precipitates were observed when the strains grew in the presence of boric acid, probably due to an adaptive response developed by the cells to the exposure, for which many proteins were differentially synthetized. This strategy to tolerate high concentrations of boron by immobilizing it in bio-precipitates has not been previously described, to the best of our knowledge, and may have a great potential application in remediating soils contaminated with boron compounds.